Priority efforts to increase income of agribusiness companies in West Bandung, West Java, Indonesia - Gandhi, Prima; Jannah, Dita Miftakhul; Nurkaidah, Dinda (Universitas Musamus, Merauke, Papua, 2023)
Horticulture is one of the agricultural sub-sectors with excellent potential to develop in Indonesia. Horticulture includes vegetables, fruits, medicinal plants, and ornamental plants. Along with the development of agricultural technology, horticultural crops can be cultivated with a hydroponic system. The hydroponic system or soilless culture is a way of cultivating plants using a solution medium. Hydroponic systems are proliferating for cultivating horticultural vegetables due to the increasing demand for quality vegetables. Vegetables cultivated using the hydroponic system are fresher and cleaner, so they have better quality than conventional vegetables. The reason is that plant roots are not in direct contact with the soil. One of the agribusiness companies that cultivate vegetables with a hydroponic system is Wangunsari Farm Hydroponics (WFH). WFH is in Lembang District, West Bandung Regency, West Java Province. WFH plans to cultivate Redoakleaf Lettuce vegetables and establish a Kale Crunch business to increase income. This study aims to analyze the financial aspects of cultivating RedOakleaf Lettuce and establishing a Kale Crunch business, and determining which business is a priority to be carried out first. The analytical method used is descriptive graphics, quantitative tabulation, and counting Net Present Value (NPV), Gross B/C, Net B/C, Internal Rate of Return (IRR), and Payback Period. Based on the financial feasibility calculations, it is concluded that both businesses are feasible for increasing WFH income. However, the Kale Crunch business has become a priority before cultivating the Red Oakleaf Lettuce vegetable because it has a value NPV IDR 27,149,410, Net B/C 4.1, Gross B/C>1 1.1, IRR>DR is 95% where DR is 3.5% and the payback period is two years where the business life is five years. Horticultural agribusiness supports the eighth Sustainable Development Goals (SDGs).